The Effect of Directed Listening Strategies on Enhancing Listening Proficiency Among Intermediate EFL Learners - Osman, Hatim Mohamed Ahmed; Alkbiri, Bayan Saleh Abdulrheem (Journal of Ecohumanism, 2024)
This study aimed to reveal the effect of the Directed Listening strategy on developing listening skills among EFL Intermediate Stage Students. The researchers employed a quasi-experimental design with two groups, experimental and control groups. The study sample consisted of (44) third-grade intermediate school female students studying English as a foreign language. The control group included (22) students, while the experimental group comprised (22). The tool was a listening skills test designed from the English curriculum prescribed for third-grade intermediate students in Saudi Arabia. The study findings indicated that using the Directed Listening strategy significantly impacted learning listening skills (comprehending ideas, understanding the speaker’s purpose, and extracting meaning) among third-grade intermediate school female students. Additionally, the Directed Listening strategy encourages students’ participation in designing educational activities, helping them connect prior knowledge with new information and predict expected new information from the text. The study recommended providing a suitable environment for implementing the Directed Listening strategy and organizing training programs for teachers to apply it effectively.